Task-Specific Training and Neuroplasticity for Stroke Recovery: Mechanisms, Interventions, and Future Directions - Furqan Ahmed Siddiqi; Saira Jahan; Muhammad Furqan Hassan; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2026)
Recent advancements in stroke rehabilitation emphasize the importance of neuroplasticity and task-specific training (TST) in facilitating motor recovery and functional outcomes in stroke survivors. Considering the global rise in stroke, particularly in developing countries like Pakistan, it is important to implement evidence-based practices that optimize post stroke recovery. TST involves repetitive practicing goal-oriented tasks. It has shown promising results in facilitating cortical reorganization and enhancing functional outcomes. TST encourages usedependent neuroplasticity by incorporating affected neural pathways through intensive, repetitive, goaldirected, purposeful activity. Studies suggests that interventions such as virtual reality-based task-specific training, robotic-assisted therapy, and constraint-induced movement therapy can improve the functional motor outcomes. In addition, technological advancements include novel, cost-effective strategies that integrate TST with digital tools to maximize patients’ compliance. Implementing TST via adaptable rehabilitation models can improve recovery and long-term quality of life for stroke survivors. This review explores TST -induced neuroplasticity, highlights key interventions, and outlines future strategies for implementation in resource-limited settings like Pakistan. Keywords: Motor Skills, Neuronal plasticity, Rehabilitation, Stroke, Task Performance.